Effect of Family Assistance During Operation on The Level of Anxiety of Sectio Caesarea Patients in RSIA Stella Maris Medan - Suherni (Caring: Indonesian Journal of Nursing Science, 2019)
Surgical action is one of the potential and actual threats to the integrity of a person who can arouse anxiety when dealing with it, so there is a need for psychological preparation when facing surgery. The most common surgical procedure is sectiocaesarea. In sectiosaesarea surgery a mother will experience anxiety, of course this can be dangerous if not handled properly. One of the treatments is with good psychological preparation that is from yourself and support from the closest family. The type of research used was observational analytic with the aim to determine the effect of family assistance during surgery on the anxiety level of Sectio Caesarea patients. The population in this study were all patients postoperative caesarean section. The sample used with the Purposive Sampling method is the technique of determining the sample based on certain considerations, the sample size is 50 respondents.The data processing tool used is SPSS 17.0 For Windows Release. The Mann-Whitney Test was used to analyze data. The results showed p-value = 0,000 (p-value <0.05) which means that there were significant differences between the anxiety levels of group patients accompanied by families with those who were not accompanied by family during sectiocaesareasurgery.It is recommended to health services, especially the Stella Maris Hospital in Medan, to continue to facilitate families to assist patients who undergo surgical procedures for caesarean section so that they can reduce the level of anxiety for patients who will undergo surgery. Researchers expect that nurses can provide emotional support and motivation to patients to improve patient self-acceptance.